2013
DOI: 10.1177/0143034313512407
|View full text |Cite
|
Sign up to set email alerts
|

Still a target: Sexual diversity and power of caring

Abstract: This study examined the link between victimization and sexual orientation and how this link contributes to social-emotional health, extending to school-related outcomes among adolescents. Of additional interest was to explore the role of having caring adult support as a protective factor to reduce the risk for high levels of distress or enhance positive aspects of life experiences. Participants included 27,245 students (14,114 girls) in grades 7-12 in Western Canada. Results of logistic regression revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…The present study revealed that low family support, but not peer support, during childhood increased the risk of suicidality in emerging adulthood among gay and bisexual men. This result is consistent with that of Konishi and Saewyc (). Previous research reported that family acceptance and support can reduce the effects of sexuality‐based discrimination (Diaz, Ayala, Bein, Henne, & Marin, ), which may partially account for the protective effect of family support in childhood on reducing suicidality in gay and bisexual men.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present study revealed that low family support, but not peer support, during childhood increased the risk of suicidality in emerging adulthood among gay and bisexual men. This result is consistent with that of Konishi and Saewyc (). Previous research reported that family acceptance and support can reduce the effects of sexuality‐based discrimination (Diaz, Ayala, Bein, Henne, & Marin, ), which may partially account for the protective effect of family support in childhood on reducing suicidality in gay and bisexual men.…”
Section: Discussionsupporting
confidence: 94%
“…Fourth, we did not examine perceived social support from sources other than families and peers. A previous study found that support from teachers could moderate the relationship of bullying victimization with social–emotional and school‐related problems in sexual minority youths (Konishi & Saewyc, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research detailed that resilience resources which are commonly known to work well for adolescents in general might be just as important for LGBTQ youth. These factors included school connectedness (Poon, Saewyc, & Chen, ; Saewyc et al., ), family support (Craig & Smith, ; Eisenberg & Resnick, ; Konishi & Saewyc, ), and knowing caring adults (Eisenberg & Resnick, ; Gastic & Johnson, ) for LGB youth, as well as school connectedness (Veale et al., ), perceived parental (Simons, Schrager, Clark, Belzer, & Olson, ; Veale et al., ), and social support (Grossman, D'Augelli, & Frank, ; Veale et al., ) for trans youth. Resilience resources unique to LGBTQ youth were identified across family, peer, school, and community contexts.…”
Section: Purpose Of the Current Studymentioning
confidence: 99%
“…A recent trend study on harassment among adolescents has shown that sexual minority students continued to report higher rates of victimization than exclusively heterosexual peers over time [29]. Victimized sexual minority youth were at greatest risk not only for mental health concerns [30][31][32].…”
Section: Associations With Mental Healthmentioning
confidence: 99%